2015
DOI: 10.1039/c4cy01183j
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced reverse water gas shift reaction over oxide supported Au catalysts

Abstract: We show that localized surface plasmon resonance (LSPR) can enhance the catalytic activities of different oxide-supported Au catalysts for the reverse water gas shift (RWGS) reaction. Oxide-supported Au catalysts showed 30 to 1300% higher activity for RWGS under visible light compared to dark conditions. Au/TiO 2 catalyst prepared by deposition-precipitation (DP) method with 3.5 nm average Au particle size showed the highest activity for the RWGS reaction. Visible light is converted into chemical energy for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 67 publications
(179 reference statements)
11
92
0
5
Order By: Relevance
“…A high E ads,O partially compensates the energy cost for C–O bond cleavage in the CHO intermediates and increases the selectivity towards CH 4 . Although the reaction on the Au catalysts has been reported to involve additional reaction intermediates225960, the selectivity observed here is consistent with the corresponding E ads,O of Rh (5.22 eV) and Au (3.25 eV)61: the Rh catalyst had a slight preference towards CH 4 production under dark conditions, whereas the Au catalyst exclusively produced CO.…”
Section: Resultssupporting
confidence: 88%
“…A high E ads,O partially compensates the energy cost for C–O bond cleavage in the CHO intermediates and increases the selectivity towards CH 4 . Although the reaction on the Au catalysts has been reported to involve additional reaction intermediates225960, the selectivity observed here is consistent with the corresponding E ads,O of Rh (5.22 eV) and Au (3.25 eV)61: the Rh catalyst had a slight preference towards CH 4 production under dark conditions, whereas the Au catalyst exclusively produced CO.…”
Section: Resultssupporting
confidence: 88%
“…[22] The authors proposed that plasmonic near-fields coupled to optical transitions, which involvel ocalised electronic states in TiO 2 ,r esulted in enhanced visible-light absorption and electron-hole pair formation, whichi mpactedp hotocatalytic H 2 production directly.O ther studies also suggest that "hot" electrons are transferred from Au into the TiO 2 conduction band. [20,21,[48][49][50] The XRD patterns for the Au/TiO 2 photocatalysts ( Figure 2F) confirmed the presence of face-centred cubic (fcc) Au nanoparticles by the appearance of weak signals at 2 q = 38.2, 44.4, 65.6, 77.6 and 81.78 ( Figure S4). [51] XRD measurements also verified that the size of the TiO 2 particles did not change after Au deposition.…”
supporting
confidence: 65%
“…It has becomeahot topic of research because of its ability to activate TiO 2 for H 2 production under visible light. [19][20][21][22][48][49][50] This new,s table way to induce visiblelight driven H 2 production relies on ac omplexi nterplay of electronic energy levels that direct charge transfera tt he Auoxide interface. Several studies have put forward experimental evidencet oe xplain the mechanism of H 2 production driven by Au SPR.…”
mentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37] Rodriguez et al studied WGS over Au/TiO 2 (110), and on the basis of experiments and theoretical calculations they concluded that the metalsupport interface is critical for the activation of water and the formation of a carboxyl intermediate which further decomposes into CO 2 and H 2 . 29 Ribeiro and co-workers elucidated the effect of the interface on water activation and determined that the WGS reaction rate scales linearly with the number of under-coordinated Au atoms, estimated from physical models of Au clusters and particle size measurements.…”
Section: Introductionmentioning
confidence: 99%